Taxonomic study and population variation of scale insects (Hemiptera: Coccidae and Diaspididae) and associated parasitoids (Hymenoptera: Chalcidoidea) in an olive grove at Rio Grande do Sul, Brazil - Wolff, Vera (2018)
This study evaluated the population variation of Hemiberlesia lataniae (Signoret) (Hemiptera: Diaspididae) and associated parasitoids in Olea europaea L. (Oleaceae) groves located in the municipality of Barra do Ribeiro (30°30′54.95″S; 51°30′20.84″W), Rio Grande do Sul, Brazil. Eight samples were collected during the four seasons from November 2015 until October 2017; four branches with approximately 20 leaves were taken from12 olive trees (four each from Arbequina, Arbosana and Koroneiki varieties). The collected material was placed inplastic bags and taken to the laboratory for further study. Scale insects were slide-mounted and were identifiedaccording to morphological characteristics of the adult female. Parts of two branches and 40 leaves of each variety infested with scale insects were sectioned and placed inside glass tubes, labeled, capped with cotton, kept in the laboratory at room temperature and examined daily to verify the emergence of parasitoids. Parasitoid specimens studied were critical point dried from ethanol and point-mounted. Some specimens were slide mounted in Canada balsam for more detailed study. In all samples, the presence of H. lataniae, as well as six associated parasitoid species, were identified. Metaphycus flavus (Howard) is recorded for the first time as a parasitoid of H. lataniae. Two other scale insects were also identified: Pseudaulacaspis pentagona (Targioni Tozzetti) (Diaspididae) and Saissetia coffeae (Walker) (Coccidae), but the population data of these did not permit statistical analysis. A key to identify the scale insect species recorded on olive trees in Brazil, based on adult females, is provided.